2016
DOI: 10.3748/wjg.v22.i5.1877
|View full text |Cite
|
Sign up to set email alerts
|

Italian survey on non-steroidal anti-inflammatory drugs and gastrointestinal bleeding in children

Abstract: The data collected in this study confirms that adverse events with the involvement of the gastrointestinal tract secondary to NSAID use are also common in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 20 publications
3
31
0
4
Order By: Relevance
“…Emerging research has shown that the main side effects of ibuprofen involve the gastrointestinal system [7] and the kidneys [8], especially in feverish dehydrated individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging research has shown that the main side effects of ibuprofen involve the gastrointestinal system [7] and the kidneys [8], especially in feverish dehydrated individuals.…”
Section: Introductionmentioning
confidence: 99%
“…La automedicación con antinflamatorios no esteroideos y opioides se ha asociado con efectos adversos renales, cardiovasculares y gastrointestinales, además del potencial de mal uso, abuso y dependencia que encierra esta práctica [9][10][11][12] .…”
Section: Introductionunclassified
“…In a study of 51 patients in Italy regarding NSAID use, the rate of associated pain was 56.9%, PUs was 13.7%, hematemesis was 33.3%, and erosive lesions was 62%. 6 In addition to its direct effects, NSAIDs can cause pyloric edema by decreasing the prostaglandin E2 levels and increasing the gastric secretions by increasing the histamine levels indirectly.…”
Section: Discussionmentioning
confidence: 99%